2015
DOI: 10.5530/fra.2015.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Anticancer Effects of 12 Iranian Herbs on Human breast Adenocarcinoma cells with antioxidant Properties

Abstract: Introduction: Many of Medicinal plants have been investigated for possible anticancer properties. The correlation cytotoxic effect of herbs with antioxidant activity is unclear, yet. The aim of the present study was to examine the antioxidant contents and anticancer effects of 12 Iranian medicinal plants on proliferation of breast cancer, MCF-7, and epithelial normal, MCf-10A, cells. Methods: Free radical scavenging and total antioxidant capacities of herbal waters assessed by DPPH and FRAP methods, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
1
6
0
2
Order By: Relevance
“…Our results were demonstrated more antioxidant, phenolic compounds and higher free radical scavenging property in OS than IOS, significantly. The high antioxidant activity of herbs is primarily due to the high levels of phenolic and caratenoid content and our observations are consisting with previous studies (14,22). In addition, HPLS data were illustrated OS extract had more amounts of active metabolites such as crocin, picrocrocin and safranal when compared to IOS, significantly (P<0.01).…”
Section: Discussionsupporting
confidence: 90%
“…Our results were demonstrated more antioxidant, phenolic compounds and higher free radical scavenging property in OS than IOS, significantly. The high antioxidant activity of herbs is primarily due to the high levels of phenolic and caratenoid content and our observations are consisting with previous studies (14,22). In addition, HPLS data were illustrated OS extract had more amounts of active metabolites such as crocin, picrocrocin and safranal when compared to IOS, significantly (P<0.01).…”
Section: Discussionsupporting
confidence: 90%
“…These plants may have some novel antibiotics, antifungal, antiparasitic, anticancer or antidiabetic compounds that may be effective for treating diseases. Recently, this genus has drawn more attention due to the anticancer effects (Al-Anee et al 2014, 2015Hoshyar et al 2015). Identification of active compounds of Hymenocrater spp.…”
Section: Discussionmentioning
confidence: 99%
“…The aerial parts of H. calycinus collected from Bojnurd in Iran are a potential source of natural antioxidants, phenolic and flavonoids; the total phenolic content and antioxidant ability were depending on the type of solvent (Soodmand et al 2015). Hoshyar et al (2015) reported the correlation of anticancer effects of H. platystegius extract on human breast adenocarcinoma cells with antioxidant properties. The aqueous extract of H. platystegius collected from South Khorasan in Iran possessing high total antioxidant activity, total phenolic content and DPPH radical scavenging activity dramatically decreased the cancer cell viability.…”
Section: Antioxidant Activity Anticancer Activity and Cytotoxicitymentioning
confidence: 99%
“…Edible plants made into herbs have been proven to not only possess antioxidant ability but also display anticancer properties. 25 Plants belonging to the Zingiberaceae family have long been used as folklore medicine to treat various ailments. In current research, we have selected three commonly edible plants from this family in search of potential free radical scavengers.…”
Section: Discussionmentioning
confidence: 99%